1991
DOI: 10.1248/cpb.39.2100
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the Biological Potency of Polychlorinated Dibenzo-p-dioxins and Their Electronic States.

Abstract: The molecular orbital (MO) method, as one approach explaining the structure-activity of polychlorinated dibenzo-p-dioxins (PCDDs), was used to understand the relationship between the biological activities and electronic state or highest occupied molecular orbital (homo) phase symmetry of PCDDs. The structure-activity relationship of PCDDs could be explained by the difference between the homo and lowest unoccupied molecular orbital (lumo) energy levels (delta epsilon: difference of epsilon homo and epsilon lumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…For example Figure 9 shows that the 140 ppm - 150 ppm, 110 ppm - 120 ppm, 2.0 Å - 2.5 Å bin is persistently occupied by carbon atoms neighboring the oxygen atoms in PHDDs, indicating the importance of oxygen atoms for binding to AhR [14,31]. Hence, the lack of oxygens in the structure of PCBs can be correlated to their weaker binding affinity (and consequently their lower molar toxicity).…”
Section: Resultsmentioning
confidence: 99%
“…For example Figure 9 shows that the 140 ppm - 150 ppm, 110 ppm - 120 ppm, 2.0 Å - 2.5 Å bin is persistently occupied by carbon atoms neighboring the oxygen atoms in PHDDs, indicating the importance of oxygen atoms for binding to AhR [14,31]. Hence, the lack of oxygens in the structure of PCBs can be correlated to their weaker binding affinity (and consequently their lower molar toxicity).…”
Section: Resultsmentioning
confidence: 99%
“…However, recently Kobayashi et al ( 15) found a correlation between logarithms of AHH activities of selected PCDDs in the liver of chicken embryo and the difference between IP and EA of individual congeners. Since most toxic PCDDs and related xenobiotics are potent AHH inducers and have high affinities for the cytosolic protein (1-7), we hypothesize that the potency of a PCDD as an AHH inducer, ECsocpcdd), has the following dependence on its affinity for AhR and IP and EA of PCDD ®^50(PCDD) ^d(PCDD) eXP[Eg(PCDD)/ (7) Where <* is the proportionality sign, Eg(pcDD> = [ IP<pcdd) -EA(pcdd) 1 and is known as the electronic energy gap (8, [15][16][17], R is the universal gas constant, and T the temperature in kelvins. Since PCDDs are structurally related compounds, ECsocpcdd) relative to EC50(tcdd> takes the form (8) where AE = Eg(pcDD> -Eg(TCDD)• As it is clear from eq 8, a PCDD is expected to be a potent AHH inducer if its affinity for AhR is high and has a smaller Eg than TCDD.…”
Section: Resultsmentioning
confidence: 99%
“…The results of experimental studies showed that polyhalogenated AXs produce similar patterns of biochemical and toxic responses in animals (1-7) and that their potencies as AHH inducers correlate with AhR mediated toxicities in mammals (1)(2)(3)(4)(5)(6)(7)(13)(14)(15). In Table IV, we compare AHH activities of some PCDDs and PCDFs relative to TCDD with corresponding toxic equivalency factors (TEFs) in animals and the average thymic atrophy and average body weight loss in rats (14).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, there are many reports on the cytotoxic effects of the hydrophobic compounds included in composite resins, such as Bis-GMA and TEGDMA or their analogues [6][7][8][9][10][11][12][13][14][15][16][17][18][19] , which is also related to the problem of environmental estrogens by bisphenol A. The relationship between the three-dimensional structure of environmental estrogens and the toxicity (biological activity) has been studied 20,21) . On the other hand, the hydrophilic compounds included in dental cements and adhesive resins such as polybasic acids, the polymers prepared from unsaturated polybasic acids, and monomers with various functional groups, play important roles in the materials, such as the hardening reaction and adhesive properties, and the materials are directly applied to dentin.…”
Section: Introductionmentioning
confidence: 99%